Harmonisasi Hukum Islam dan Syariat dalam Prinsip Negara Hukum Modern Indonesia - Ansar, Lukman; Hasmiyati, Hasmiyati; Zulfadli, Zulfadli; Tarmizi, Tarmizi (IAIN BONE, 2025)
This article examines the alignment between Islamic law and positive law in Indonesia as a constitutional state. It aims to re-map the contemporary application of Islamic law in Indonesia by employing an empirical juridical method based on existing legal products in the country. The article emphasizes that harmonizing Islamic law with the principles of the rule of law in Indonesia is a complex process that requires balancing normative legitimacy, social acceptance, and respect for democratic values and human rights. The experience of Aceh, particularly through the implementation of the Qanun Jinayat, demonstrates that the integration of sharia into the national legal system is possible, yet still demands regulatory synchronization, inclusive public participation, and adaptive interpretations of sharia oriented toward public welfare. Therefore, continuous dialogue, interinstitutional coordination, strengthened judicial capacity, and investment in moderate legal education are essential to ensure that Islamic law can contribute constructively to the national legal mosaic without compromising substantive justice or the diversity guaranteed by the constitution. With these measures, legal harmonization does not remain merely a normative discourse but is realized in sustainable practices responsive to the needs of modern society.